Oxidation–reduction and heterocyclization of the reactions of alkanedithiols with π-deficient compounds. (4th May 2017) - Aly, Ashraf A.; Bräse, Stefan
ABSTRACT: The reaction of 1, 2-ethanedithiol and 1, 3-propanedithiol with π-deficient compounds afforded various oxidation–reduction and cyclized products under mild conditions. Heterocycles containing one sulfur atom ( e.g. analogues of seriniquinone) were also obtained. The structures of the products were elucidated by NMR, IR, mass spectral data, and elemental analyses. The mechanisms were also discussed. GRAPHICAL ABSTRACT: